If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y-2=9y+4
We move all terms to the left:
6y-2-(9y+4)=0
We get rid of parentheses
6y-9y-4-2=0
We add all the numbers together, and all the variables
-3y-6=0
We move all terms containing y to the left, all other terms to the right
-3y=6
y=6/-3
y=-2
| 18^2+b^2=24^2 | | -7x+2=-2x+27 | | X/5+1=y | | 2(-1x-1)=-12 | | 5x-18+14x+45=180 | | 6x+6=136-7x | | X-2/4+x+8/3=44 | | 6-5x=3x-58 | | 6(6x-2)=21 | | J=9(-8+3)j= | | 2x-x/2=50 | | 6^3x=1296 | | -2x-4=-3x+5 | | 6(-4x-9)=210 | | k/7+8=14 | | 22−2p=14 | | 36+3.50x=4.25x | | s9+ 26= 32 | | 6g+29=95 | | 12x+23x=5 | | 2(y+18)=78 | | 4(1x+5)=52 | | 99=9(y+2) | | w^2+4w-76=0 | | 9-4y=18 | | x+1=3^x-2 | | -3(7x+9)=-90 | | -3x-7=-13 | | 3u/8=21 | | -3(7x-9)=-90 | | 6-11z=4 | | 0.33333333x=0.5x-1.5 |